Pengabdian Kepada Masarakat (Pkm) Peningkatan Minat Melanjutkan Studi Bagi Siswa Kelas Xii Ma Nu Sunan Ampel Beji Pasuruan - Laila, Itsna Noor (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
This Community Service (PkM) aims to increase the motivation and interest of class XII students at MA Nahdlatul Ulama Beji Pasuruan to continue their studies at tertiary level. The small interest of students in continuing their studies at tertiary level in the Beji Pasuruan area is the background for carrying out this activity. Based on the results of observations made, most of the final year students want to become factory workers when they graduate from school, while others, especially female students, want to marry young. This certainly causes unrest in the hearts of education observers. Therefore, the implementation of this educational seminar aims to provide discourse that continuing to studi at university is an alternative for improving the standard of living of the younger generation and building a quality society in the future. The result of this PkM activity is to open the insight of class become world citizens.